Z gibanjem do zdravja - od otroka do starostnika - Pišot, Rado (Zdravstveno varstvo, 2002)
Many research findings prove that active lifestyle and physical exercise are important factors in health protection. Physical activity prevents from developing the majority of chronic non-contagious diseases such as atherosclerosis, hypertension, stroke, insulin independent diabetes, osteoporosis etc. Epidemiological data show that physical inactivity presents at least twice as risk factors for the development of coronary diseases, similarlyas other main known risk factors for atherosclerosis (high cholesterol level, smoking and hypertension). Physical activity brings into action direct mechanisms (affecting the cardiovascular system) and indirect mechanisms (affecting the known risk factors) and thus decreases the morbidityand mortality from cardiovascular diseases. An important improvement of our health, as well as a longer life expectancy, result from all forms of movement and physical exercise performed over a longer period of time. Therefore, we advise healthy people, as well as sick ones, such kind of exercise that they prefer the most, that can be included easily into their daily routine and that suits their physical fitness, age and health condition.It has been proven that regular physical activity protects health ofall age groups. However, particular attention must be devoted to the beginning of the adult age, when most people give up physical activity and begin living a sedentary lifestyle.
Keywords: adult; gibalna aktivnost; gibanje; health; motor activity; motorika; odrasli; zdravje; zdravo življenje